2023
DOI: 10.3390/pathogens12070881
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine Detected in Strains of Staphylococcus aureus

Abstract: Most forms of life, including the archaea, bacteria, and eukaryotes synthesize the polyamine putrescine. Although putrescine is widely distributed, several Gram-positive bacteria, including Staphylococcus aureus (S. aureus), appear to be the exceptions. We report here that strains of S. aureus can produce the polyamine putrescine, as well as the derivative N-acetyl-putrescine. Three strains of S. aureus from the American Type Culture Collection (ATCC), one strain listed in the National Center for Biotechnology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, there may be other strains of these organisms that are not in the IMG database that do possess the enzymes to generate putrescine. For example, one study found that S. aureus strains BAA‐44, ATCC 43300, and ATCC 25293 were able to generate putrescine (Seravalli & Portugal, 2023 ). This study found that S. aureus ATCC 25293 was able to generate the highest concentration of putrescine; suggesting that some strains may be better at generating and secreting this product.…”
Section: Discussionmentioning
confidence: 99%
“…However, there may be other strains of these organisms that are not in the IMG database that do possess the enzymes to generate putrescine. For example, one study found that S. aureus strains BAA‐44, ATCC 43300, and ATCC 25293 were able to generate putrescine (Seravalli & Portugal, 2023 ). This study found that S. aureus ATCC 25293 was able to generate the highest concentration of putrescine; suggesting that some strains may be better at generating and secreting this product.…”
Section: Discussionmentioning
confidence: 99%